Taxonomy and Molecular Phylogeny of Two New Species of Prostomatean Ciliates With Establishment of Foissnerophrys gen. n. (Alveolata, Ciliophora) - Jiang, Limin; Zhuang, Wenbao; El-Serehy, Hamed A.; Al-Farraj, Saleh A.; Warren, Alan; Hu, Xiaozhong (Frontiers in Microbiology, 2021)
Prostomatean ciliates play important roles in the flow of material and energy in aquatic microbial food webs, and thus have attracted wide attention for over a century. However, the taxonomy and systematics about them are still poorly understood because of their relatively few taxonomically informative morphological characters. In this study, two new prostomateans, Lagynus binucleatus sp. n. and Foissnerophrys alveolata gen. n., sp. n., collected from a freshwater pool and the intertidal zone of a sandy beach respectively in Qingdao, China, are investigated using living observation, protargol-staining, and SSU rRNA gene sequencing methods. Here, we redefined the genus Lagynus and described a new species of it based on significant morphological differences with similar forms. Furthermore, a new genus, Foissnerophrys was established based on a combination of previous and present studies. The identities of intracellular prokaryotes of these two new species are discussed based on fluorescence in situ hybridization (FISH) data and newly obtained 16S rRNA gene sequences.